SISTEM PENGELOLAAN KENDARAAN DINAS DI PEMERINTAH KOTA SALATIGA - Alfiyanus Shaf’at; Dwi Retnoningsih; Hardika Khusnuliawati (Universitas Sahid Surakarta, 2020)
The optimal management of regional property has become a basic requirement for local governments in realizing good governance. Official vehicles as one part of regional property have a significant function. However, the process of managing official vehicles in regional organizations of Salatiga government is still not optimal. For example, the frequency of vehicle maintenance schedules are missed and vehicle tax payments are due. The change of official vehicle users also often occurs and it will be a problem if the process is not recorded properly. This study aims to design an applications in supporting regional organizations at Salatiga government for managing data and presenting information related to official vehicles. This study used the Linear Sequential Model / Waterfall Model. The data collection covered observation, interviews and literature study. The application wasmade in the form of a desktop application using the Node.js platform and it is based on javascript and utilizes the electron framework. The database used SQLite. Analysis and design of the system used a structured method through the stages of making normalization, relations between tables, entity relationship diagrams, data dictionaries, data flow diagrams, flowcharts, and interface design. The resulting application is tested using the blackbox testing method. The analysis of test results shows that the application is functioning normally according to the expected results. The main function of managing data on the use and maintenance of official vehicles has been successful through all the test scenarios conducted.